Local Activation of Cannabinoid CB1 Receptors in the Urinary Bladder Reduces the Inflammation-Induced Sensitization of Bladder Afferents. Issue 1 (9th May 2011) - Walczak, Jean-Sébastien; Cervero, Fernando
Background: Systemic administration of cannabinoid agonists is known to reduce pain induced by bladder inflammation and to modulate cystometric parameters in vivo . We have previously reported that intravesical administration of a cannabinoid agonist reduces the electrical activity of bladder afferents under normal conditions. However, the effects of local activation of bladder cannabinoid receptors on afferent activity during inflammation are unknown. This study was aimed to assess the effects of intravesical administration of a cannabinoid agonist on the discharges of afferent fibers in inflamed bladders ex vivo . We also characterized the expression of CB1 receptors in the bladder and their localization and co-expression with TRPV1, a marker of nociceptive afferents. Results: Compared to untreated animals, afferent fiber activity in inflamed bladders was increased for intravesical pressures between 10 and 40 mmHg. Local treatment with a non selective cannabinoid agonist (AZ12646915) significantly reduced the afferent activity at intravesical pressures above 20 mmHg. This effect was blocked by AM251 but not by AM630 (selective for CB1 and CB2 respectively). Finally, CB1 was co-expressed with TRPV1 in control and inflamed bladders. Conclusion: These results demonstrate that sensitization of bladder afferents induced by inflammation is partly suppressed by intravesical activation of cannabinoid receptors, an effect that appears to be mediated by CB1 receptors. Also, TRPV1 positive fibers were found to co-express CB1, supporting the hypothesis of a direct action of the cannabinoid agonist on nociceptive afferents. Taken together, these results indicate a peripheral modulation by the cannabinoid system of bladder hypersensitivity during inflammation.